Abusive supervision and frontline employees' attitudinal outcomes: The multilevel effects of customer orientation. Issue 3 (13th April 2020) - Al-Hawari, Mohd Ahmad; Bani-Melhem, Shaker; Quratulain, Samina
Abstract : Purpose: This study aims to examine a moderated mediation model that explains how abusive supervision influences employees' capacity to satisfy customers (via their silence behavior) and how a customer-oriented work climate moderates the indirect influence of abusive supervision on frontline employees' (FLEs) capacity to satisfy customers. Design/methodology/approach: A time-lagged design was used to collect data from 335 FLEs of 57 hospitality organizations. A multilevel analysis was performed to test the hypotheses underpinning the study. Findings: The findings revealed that employees are more likely to remain silent when they experience abusive supervision and this silence directly affects their ability to serve customers. The effect that abusive supervision has on silence behaviors is stronger when organizational customer orientation is low. Practical implications: The study findings can provide hospitality managers with a better understanding of the complex relationship between supervisory behaviors and the organizational environment and how these factors influence employees' discretionary behaviors (e.g. decision to intentionally withhold information) and capacity to serve customers. Originality/value: The findings provide a novel contribution by explaining how abusive supervision affects hospitality employees' capacity to serve customers and when this effect is more pronounced. These findings highlight that hospitality organizations need to understand that when leader behavior does not align with what is prescribed for a customer-oriented service climate, the benefits of a favorable work climate do not exist.